Schools and neighborhoods: Moderating the counter-delinquency effect of school belonging with perceived collective efficacy - Walters, Glenn D. (Journal of criminology, 2022)
The purpose of this study was to determine whether perceived collective efficacy moderated the prospective relationship between school belonging and delinquency. Analyses were performed on a sample of 4048 youth (2020 boys, 1936 girls) from the Longitudinal Study of Australian Children (LSAC-K). Linear and negative binomial regression analyses performed with maximum likelihood (ML) and maximum likelihood with robust standard errors (MLR) estimators produced consistent results. Bootstrapped and normal theory analyses disclosed a significant interaction between school belonging and collective efficacy after age, sex, indigenous status, physical condition of dwelling, physical condition of surrounding housing, household income, weak parental monitoring, perceived peer delinquency, and prior delinquency were controlled. Further review of the significant interactive effect revealed that the increased levels of school belonging predicted decreased levels of future delinquency, but only when perceived collective efficacy was also elevated. These results support the presence of a small but significant conditional promotive effect.